The User Pays’s Principle and the Electricity Sector: A South African Case - Maphosa, Michael (Journal of Economics and Behavioral Studies, 2018)
This paper discusses the user pays’s principle (UPP) within the South African developmental state concept. The essence of the paper is to ascertain whether UPP can be implemented in the electricity sector without necessarily harming the developmental state agenda taking into account the challenges of inequality, unemployment and poverty in South Africa. In this paper, we present the arguments in support of the UPP in the electricity supply industry (ESI) and its building blocks. The paper analyses the role of regulatory authority in the implementation and adoption of the UPP. Finally, the paper analyses the role of UPP in the developmental state concept and the challenges of implementing it. The analysis shows that adoption of inclining block tariff (IBTs) was based on the individual’s perceived ability to pay and not on UPP while the free basic electricity (FBE) policy is a government-funded initiative meant to provide electricity to poor households. The paper also found that the ESI currently has high levels of inefficiencies in production and use, procurement and operation of utilities, cross-subsidisation, infrastructure and maintenance backlogs which may hinder the full implementation of UPP. Lastly, although the full implementation of UPP could incentivise efficient operation of the ESI and attract the much-needed investment in the sector, the UPP system will pose serious challenges considering the countryâ€™s three main problems: inequality, unemployment and poverty.